2014
DOI: 10.1096/fj.13-247148
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid induces endothelial dysfunction by vascular insulin resistance associated with the impairment of nitric oxide synthesis

Abstract: Endothelial dysfunction is defined as impairment of the balance between endothelium-dependent vasodilation and constriction. Despite evidence of uric acid-induced endothelial dysfunction, a relationship with insulin resistance has not been clearly established. In this study, we investigated the role of vascular insulin resistance in uric acid-induced endothelial dysfunction. Uric acid inhibited insulin-induced endothelial nitric oxide synthase (eNOS) phosphorylation and NO production more substantially than en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(128 citation statements)
references
References 44 publications
9
104
1
7
Order By: Relevance
“…In vitro studies are necessary to determine the potential deleterious effect of XO on the vascular wall, especially on endothelial dysfunction as it has already been described for uric acid [31. ]…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies are necessary to determine the potential deleterious effect of XO on the vascular wall, especially on endothelial dysfunction as it has already been described for uric acid [31. ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated serum uric acid levels and gout are associated with other cardiometabolic risk factors in diverse populations (76)(77)(78). A substantial body of work suggests that increased uric acid levels may independently regulate important aspects of metabolism and contribute to cardiometabolic risk (79)(80)(81)(82)(83). However, Mendelian randomization studies do not strongly support a causal role for circulating uric acid in mediating cardiometabolic disease (84).…”
Section: Genetic Lessons About Fructose Metabolismmentioning
confidence: 99%
“…SUA levels are also considered to be an independent risk factor for the incidence of type 2 diabetes (T2D) [9]. High SUA concentrations commonly precede the development of insulin resistance [10,11] in experimental studies [12]. Thus, several authors have suggested that hyperuricemia may be a new marker for metabolic syndrome (MetS) [13].…”
Section: Introductionmentioning
confidence: 99%